Breaking the binary: Gender versus sex analysis in human brain imaging - Rauch, Julia M.; Eliot, Lise (NeuroImage (Orlando, Fla.), 2022)
•Brain sex differences have been extensively catalogued but have yet to identify clear neural correlates of male-female behavioral difference.•Some neuroimaging has found greater success linking brain to behavior using non-binary measures of “gender” as an independent variable.•Recent advances in operationalizing “gender” will enhance discovery of neural processes underlying behavior and mental health. Despite decades of pursuit, human brain imaging has yet to uncover clear neural correlates of male-female behavioral differences. Given that such behavior does not always align with sex categories, we argue that neuroimaging research may find more success by partitioning subjects along nonbinary gender attributes in addition to sex. We review the handful of studies that have done this, several of which find as good or better association between brain measures and “gender” as they do with “sex.” Recent advances in operationalizing “gender” as a multidimensional variable should facilitate such studies, along with discovery-based approaches that mine brain imaging data for gender-associated attributes, independent of sex.